ChemInform Abstract: Alkenes as Azido Precursors for the One‐Pot Synthesis of 1, 2, 3‐Triazoles Catalyzed by Copper Nanoparticles on Activated Carbon. Issue 38 (30th August 2013) - Alonso, Francisco; Moglie, Yanina; Radivoy, Gabriel; Yus, Miguel
Abstract The first one‐pot transformation of unactivated alkenes to 1, 2, 3‐triazoles including two click steps is reported.